1996
DOI: 10.1080/026990596124502
|View full text |Cite
|
Sign up to set email alerts
|

Post-concussive syndrome: paraclinical signs, subjective symptoms, cognitive functions and MMPI profiles

Abstract: In order to investigate the organic and psychogenic components of post-concussive syndrome (PCS), the subjective complaints, the cognitive findings and the Minnesota Multiphasic Personality Inventory (MMPI) profiles of 53 consecutive mild head injury patients (MHI) with persistent PCS were evaluated. The results seem to suggest the presence of two groups: in the first, minimal lesional signs were associated with more prolonged loss of consciousness (LC) and post-traumatic amnesia (PTA), as well as an MMPI prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
1

Year Published

1996
1996
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 18 publications
2
9
1
Order By: Relevance
“…This is consistent with clinical studies showing long-term effects of mild HI [22,23,34]; however, other research has not demonstrated an association between such symptoms and reported HI [7,37]. Furthermore, postconcussion syndrome is a controversial area, with some data suggesting it is associated with psychologic characteristics independent of severity of head trauma [38].…”
Section: Discussionsupporting
confidence: 85%
“…This is consistent with clinical studies showing long-term effects of mild HI [22,23,34]; however, other research has not demonstrated an association between such symptoms and reported HI [7,37]. Furthermore, postconcussion syndrome is a controversial area, with some data suggesting it is associated with psychologic characteristics independent of severity of head trauma [38].…”
Section: Discussionsupporting
confidence: 85%
“…Secondly, cognitive symptom report was associated with higher awareness for experiencing internal bodily sensations in general which supports the assumption that a heightened self-focus may perpetuate postconcussional sequealae [63]. Unlike other studies, however, patient with and without cognitive complaints reported equal levels of neuroticism [25,29,30].…”
Section: Discussionsupporting
confidence: 67%
“…For example, the presence of depressed mood and anxiety strongly relates to subjective cognitive complaints [26][27][28]. In addition, premorbid personality characteristics like neuroticism seem to make some individuals more prone to experiencing cognitive problems than others [25,29,30]. In MTBI patients, more knowledge is needed about the influence on cognitive system report of potentially relevant forms of emotional distress such as posttraumatic stress, or traits like Type D personality or the disposition to focus on internal bodily sensations [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…For example, state factors like anxiety, depression or fatigue, which are all common in MTBI patients, may decrease effort level [23][24][25]. In addition, trait factors like individual personality structure or general intelligence may be associated with differences in performance style and as such may influence effort level [26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%